Changes in biochemical analytes in female dogs with subclinical Ancylostoma spp. infection. Issue 1 (December 2016) - Schmidt, Elizabeth; Tvarijonaviciute, Asta; Martinez-Subiela, Silvia; Cerón, José; Eckersall, Peter
Abstract Background Ancylostoma spp. is one of the most prevalent canine intestinal nematode infections which usually causes subclinical disease in adult dogs and has zoonotic implications. Therefore, the aim of this study was to explore and evaluate the possible pathophysiological changes thatAncylostoma spp. could produce in female dogs naturally infected but without clinical signs of disease, by screening a wide variety of biochemical markers for potential changes. Samples of feces and blood of 45 dogs were collected and fecal flotation and zinc sulphate centrifugal flotation were performed. The biochemical analytes determined were: the acute-phase proteins C-reactive protein (CRP) and haptoglobin (Hp); the lipid profile (cholesterol, triglycerides, HDL, LDL); the serum iron profile: iron, unsaturated iron binding-capacity (UIBC), and ferritin; the enzyme butyrylcholinesterase (BChe); the pancreatic profile: amylase, lipase, and trypsin-like immunoreactivity (TLI); the oxidative stress markers: total antioxidant capacity (TAC) and paraoxonase −1 (PON-1), along with total protein, albumin, and insulin-like growth factor – 1 (IGF – 1).Ancylostoma spp. eggs were detected in 29/45 dogs (64.4 %). Dogs were divided into two groups according to the results of fecal flotation methods. Group 1: negative fecal floatation (n = 16), and Group 2: subclinical infection with the observation ofAncylostoma spp. type eggs/x 40 objective fields (n = 29). Results Mann–WhitneyU test was used to compare the biochemical analyte results between the two groups (P < 0.05). Significant increases in CRP (μg/mL) (median): non-infected dogs: 5.5; subclinically infected dogs 18.7;P = 0.03, Hp (g/L) (median): G1: 2.4; G2: 3.3;P = 0.03, and UIBC (μg/dL) (median): non-infected dogs: 139.4; subclinically infected dogs: 216;P = 0.0015, and significantly decreased iron (μg/dL) (median): non-infected dogs: 202.5; subclinically infected dogs: 125.7;P = 0.0041, IGF-1 (ng/mL) (median): non-infected dogs: 224; subclinically infected dogs: 123;P = 0.02, and albumin (g/dL) (median): non-infected dogs: 2.8; subclinically infected dogs: 2.5;P = 0.04 concentrations were observed in dogs with subclinicalAncylostoma spp. infection when compared to non-infected dogs. Conclusion These findings provide an overview of the biochemical effects produced by patentAncylostoma spp. in naturally infected dogs without any evident clinical signs of disease, which could be considered in differential diagnosis, especially in an endemic area for this parasite.